A study on balance assessment according to the levels of difficulty in postural control - Kang, Dong-Won (J Phys Ther Sci, 2016)
[Purpose] This study aimed to determine appropriate measures for assessing balance ability according to difficulty level during standing tasks. [Subjects and Methods] The subjects were 56 old (>65 years) and 30 young (20–30 years) adults. By using the Berg balance scale, the subjects were divided into three groups: 29 healthy older (Berg score≥52), 27 impaired older (Berg score≥40), and 30 healthy young (Berg score≥55). One inertial measurement unit sensor was attached at the waist, and the subjects performed standing tasks (1 min/task) with six difficulty levels: eyes open and eyes closed on firm ground, one foam, and two foams. Thirty-nine (24 time-domain, 15 frequency-domain) measures were calculated by using acceleration data. The slope of each derived measure was calculated through the least-squares method. [Results] Five (95% ellipse sway area, root mean squares [anterior-posterior and resultant directions], and mean distance [anterior-posterior and resultant directions] in time domain) of the 39 measures showed significant differences among the groups under specific standing conditions. The slopes of derived measures showed significant differences among the groups and significant correlations with the Berg scores. [Conclusion] The slope according to the difficulty level can be used to assess and discriminate standing balance ability.